IMPROVING PRODUCTIVITY IN THE NEWSROOM?: Deskilling, reskilling and multiskilling in the news media. (16th November 2016) - Bro, Peter; Hansen, Kenneth Reinecke; Andersson, Ralf
Abstract : In an attempt to produce more news stories, faster and on different platforms, the national Danish Broadcasting Corporation, DR, has introduced a new workflow. This new workflow is based on principles and practices known internally as "the news engine, " and it has brought with it changes in regards to both the news products, the news processes and the individual news producers. This article is based on newsroom observations, interviews with employees and content analyses, and it shows how the practice of journalism at DR News has been altered in several ways after the implementation of the news engine. The changes in DR News have become the inspiration for other television stations, and the study concludes by discussing how this particular workflow affects the profession of journalism. Rather than a proletarianization of the profession, this study points to a polarization where some journalists experience a deskilling and a decrease in autonomy, while others experience an increase in autonomy as part of a process of reskilling and multiskilling.